2012
DOI: 10.1590/s0034-89102012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Decisões judiciais sobre acesso aos medicamentos em Pernambuco

Abstract: OBJECTIVE:To analyze decisions from the legal system concerning the population's access to medicines within the Brazilian Public Health System through judicial channels, with regard to decision-making criteria and possible political and economic pressure. METHODS:This was a descriptive retrospective study on documents with a quantitative and qualitative approach. Data were gathered from the State of Pernambuco Superintendency for Pharmaceutical Care, and the data sources used were 105 lawsuits and administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
6
0
7
Order By: Relevance
“…In addition, 80% of these drugs were manufactured by eight pharmaceutical companies, and 90.95% of the funds from the Pernambuco State Health Department (SES-PE) for purchasing these drugs went to just seven laboratories 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 80% of these drugs were manufactured by eight pharmaceutical companies, and 90.95% of the funds from the Pernambuco State Health Department (SES-PE) for purchasing these drugs went to just seven laboratories 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 2,5,6,12 (23,5%) analyzed the plaintiffs' allegations in the lawsuits, or the grounds for the suit. The main claims involved urgency in the patient's health condition, imminent risk of death, and prescriptions and/or medical and laboratory reports proving the need for the product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles of Marques and Dallari 57 and Vieira 98 can be considered milestones in that field. Subsequently, several articles on legal demands for medications in many States of Brazil 22 , 53 , 90 were published. The relations between the productive sector of medications with high technological incorporation and the legal system were unveiled by Chieffi and Barata 20 , which identified that a small number of lawyers answered by most of the lawsuits filed against SUS.…”
Section: Resultsmentioning
confidence: 99%
“…Nesse sentido, diversos estudos e debates começam a surgir com intuito de dar suportes teóricos para a delimitação de marcos jurídico-legais da saúde destacando-se pesquisas realizadas no município de São Paulo (Wang et al, 2014), Pernambuco (Stamford;Cavalcanti, 2012), Minas Gerais (Machado et al, 2011), Rio de Janeiro (Messeder et al, 2005), Alagoas (Macêdo et al 2015), Santa Catarina (Pereira, 2010), dentre outros, todos voltados para a compreensão do fenômeno da judicialização, traçando o perfil dos processos, natureza das demandas, fazendo inferências sobre as causas, caracterizando os diversos aspectos envolvidos e apontando para possíveis alternativas ao problema.…”
unclassified